The Effect of Progressive Muscle Therapy to Reduce Hypertension in Mr. A in the Lotus Room of Wonosari Hospital - Astuti, Winanthi surya; Putra, Muhammad Ganang (Syntax Corporation Indonesia, 2023)
Background: As one of the most important public health problems in the world, hypertension is known as a silent killer so patients are unaware of the severity of hypertension. Hypertensive conditions cause an increase in blood pressure of more than 140/90 mmHg. Kidney failure, myocardial infarction, encephalopathy (brain injury), and seizure stroke are some of the complications that often occur due to hypertension. Progressive muscle relaxation therapy is able to lower blood pressure by relaxing by recognizing tense muscles and then releasing tension in the muscles Objective: To determine the Effect of Progressive Muscle Therapy to Reduce Hypertension in Mr. A in the Lotus Room of Wonosari Hospital. Method: Descriptive case study, namely using a series of nursing processes on individuals including assessment, diagnosis, intervention, implementation, and evaluation. The research subjects are determined based on inclusion and exclusion criteria. It was determined that as many as 1 subject met the criteria to then conduct research. Results: The results of the application of non-pharmacological techniques of hypertension using Progressive Muscle Therapy, carried out for 3 days. The results of the management were obtained that there was a decrease in blood pressure from 170/90 mmhg to 130/80 mmhg. Conclusion: The implementation of nursing in Mr. A is effective by providing techniques to provide an influence on Progressive Muscle Therapy. Able to reduce hypertension with an average decrease for 3 days (8.3/3.3mmHg).